Febrile Seizures: Clinical Factors Influencing the Length of Hospital Stay - Deniz, Yusuf (The European Research Journal, 2026)
Objectives: This study aimed to identify the clinical factors influencing the length of hospital stay (LOS) in children aged 0–60 months hospitalized with febrile seizures (FS), and to explore potential immunological and psychosocial modulators that may affect hospitalization decisions. Methods: A retrospective observational study was conducted at a tertiary hospital in Karabük, Türkiye, between September 2023 and September 2025. Medical records of patients diagnosed with FS (ICD-10 R56.0) were reviewed using the FONET and e-Nabız systems. Demographic and clinical variables - including age, sex, fever, seizure duration, type (simple/complex), recurrence, infection focus, and presence of seasonal allergic rhinitis (SAR) - were analyzed. Factors associated with LOS were evaluated using multivariable linear regression (P<0.05). Results: A total of 93 children (53.3% male, mean age: 24.6±13.7 months) were included. The mean LOS was 48.2±44.7 hours. Regression analysis showed that recurrence and SAR were associated with shorter LOS (P=0.062 and P=0.065, respectively), while seizure duration and prematurity had no significant effect. Bronchitis, otitis, and tonsillitis were linked to longer stays, whereas acute gastroenteritis and mild upper respiratory infections were linked to shorter ones. Family history was strongly associated with recurrence but not with LOS. Conclusions: Hospital stay in FS is influenced more by immunological and psychosocial dynamics than by traditional demographic factors. The presence of SAR may act as a modulatory condition reducing LOS, possibly through pre-activated immune regulation. Family experience appears to facilitate earlier discharge. Integrating these factors into clinical decision-making may improve resource use and standardize hospitalization criteria.